Croup : A primer - Max Klein (AOSIS, 1990)
Croup is the single most common cause of death from airway obstruction, taking all ages into account. The patient's general appearance is an extremely unreliable guide to the severity of the obstruction in croup and specific signs must be used in the assessment. Management is discussed. It is emphasized that chest physiotherapy is specifically contra-indicated in conservatively managed children with croup. But in children who have had artificial airways inserted for life-threatening airway obstruction regular intensive chest physiotherapy is essential.